Chloride treatment for highly efficient aqueous-processed CdTe nanocrystal-based hybrid solar cells. Issue 41 (10th October 2018) - Yao, Shiyu; Liu, Leijing; Zeng, Qingsen; Du, Xiaohang; Im, Chan; Liu, Yi; Zhang, Hao; Yang, Bai; Cui, Tian; Tian, Wenjing
Abstract : This work investigated the influence of chloride treatment on aqueous-processed CdTe nanocrystal-based hybrid solar cells. Abstract : This work presents the influence of chloride treatment on the photovoltaic performance, microstructure, charge carrier dynamics, and surface chemical composition of aqueous-processed CdTe nanocrystal (NC)-based hybrid solar cells (HSCs). By applying CdCl2 treatment on the CdTe films through a spin-coating method, the power conversion efficiency (PCE) of the HSCs is largely improved from 4.49% to 6.01%. We show that the main role of chloride treatment is to promote the grain growth of the CdTe NCs, which leads to an increase in charge carrier lifetime. It is also demonstrated that CdCl2 treatment can prevent the generation of detrimental surface oxides and improve the wettability of the CdTe films.